Development of Mathematics Teaching In Elementary School Using Travel Game Media on the Material of Fractional - Siti Mulyani; Novita Damayanti; Lukman Khakim (Universitas PGRI Semarang, 2025)
This study aims to overcome the difficulties elementary school students have in understanding the abstract concept of fractional equivalence, in which only 45% (23 out of 51 students) achieved the Minimum Completion Criteria (KKM). The innovation developed is the Travel Game learning media, an adventure-based educational game that involves moving around while solving mathematical problems or challenges. The development method used is an adaptation of the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. In the Travel Game context, students are divided into groups, roll dice, and move pawns, as well as answer questions about fractional equivalence at certain stations to reach the finish line. The results showed that the use of the Travel Game media provided positive results. The number of students who achieved the KKM increased significantly from 23 to 40 students. The increase in students' understanding of fractional equivalence reached 78%. Overall, the use of the Travel Game proved effective because it suits the characteristics of elementary school students who enjoy playing while learning, fosters motivation, and creates an active and enjoyable learning atmosphere. Teachers also observed that this media facilitates the explanation of the concept of fractional equivalence.